Influência da densidade e da altura de edificações na transformação de precipitação-escoamento utilizando chuva simulada em modelo reduzido de bacia hidrográfica urbana com diferentes declividades - Reis, Simone Siqueira Dos (2015)
The increase in urban population has been observed worldwide in recent decades, without the required planning, it has provided, among other consequences, increased waterproofing surfaces, resulting increase in the volume drained rain water surface. The realization of experiments in life-size bowls, despite providing the exact information of the intervening variables (e.g. slope, area, rainfall intensity), does not allow the control of the same and therefore there is no repeatability of information. In order to prepare the transformation of rainfall-runoff studies, we developed a simulator pressurized showers and a reduced physical model, which simulates a sealed urban watershed where you can control the longitudinal and transverse slope of the surface, unprecedented assembly in Brazil. In this sense it was aimed to investigate the hydrological response of the influence of transverse and longitudinal slope of the land, the density and height of buildings in runoff in fully waterproofed urban areas. Much of this research effort was the development and calibration of the rain simulator, whose assembly has resulted in a spatial uniformity coefficient of 78.63% and an average intensity of 78.82 mm∙ h-1 rainfall. A total of 30 scenarios with combinations of different slopes, density and height of buildings. The transverse slopes ranged from 2.5% to 5.0% and longitudinal 2.5%, 5.0% and 10.0%. The densities ranged from zero buildings, 15% and 30% of the template area and the heights of the buildings varied in 15 cm and 30 cm. The addition of the longitudinal slope of 2.5% to 5.0% caused an increase of 52.50% in hydrogram rise time and the combination of the highest density setting constructions and buildings of greater height and an increase of the concentration-time 55.00%, suggesting a slower hydrological response due to the increase the height of buildings.